Protective Behavior in Course of the COVID-19 Outbreak-Survey Results From Germany - Daniel Lüdecke; Olaf von dem Knesebeck (Frontiers Media S.A., 2020)
Objective: The COVID-19 outbreak means far-reaching changes in the organization of daily lives. Disease-related literacy and factors such as age, gender, or education play a major role in shaping individual practices of protective behavior. This paper investigates different types and frequency of practicing protective behaviors, as well as socio-demographic factors that are associated with such behavioral change.Methods: Data stem from a cross-sectional survey in Germany. Three thousand seven hundred and sixty-five people were contacted, 3,186 participated in the survey. Information on behavior to lower the risk of becoming infected with COVID-19 was assessed by nine items (answer options yes/no). For each item, logistic regression models were used to estimate odds ratios (OR), using education, sex, and age as main predictors and adjusting for partnership status and household composition.Results: People with lower educational level were less likely to avoid gatherings (OR = 0.63; 95%CI = 0.48-0.83), adapt their work situation (OR = 0.66; 95%CI = 0.52-0.82), reduce personal contacts and meetings (OR = 0.71; 95%CI = 0.55-0.93), or increase hand hygiene (OR = 0.53; 95%CI = 0.38-0.73). Being female was associated with higher odds of protective behavior for most outcomes. Exceptions were wearing face masks and adapting the own work situation. Associations between respondents' age and individual behavior change were inconsistent and mostly weak.Conclusion: Disease specific knowledge is essential in order to enable people to judge information on COVID-19. Health education programs aiming at improving COVID-19 knowledge are helpful to build up appropriate practices and reduce the spread of the disease. Strategies are needed to guarantee easy access and better dissemination of high-quality news and fact-checks. Socioeconomic characteristics should be taken into account in the development of infection control measures.